2013
DOI: 10.1155/2013/570954
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case Report of Erupted Odontoma

Abstract: Odontomas are the most common of the odontogenic tumors of the jaws, which are benign, slow growing, and nonaggressive. They are usually asymptomatic and found in routine dental radiographic examination. Odontomas are usually associated with tooth eruption disturbances. Eruption of odontoma in oral cavity is rare entity. Here we report a case of an unusual erupted compound odontoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 5 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Odontoma is the most common type of odontogenic tumor or hamartoma (not a true . [5] Hitchin suggested that odontomas inherited through a mutant gene or interference, possibly postnatal, with genetic control of tooth development. In humans, there is a tendency for the lamina between the tooth germs to disintegrate into clumps of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontoma is the most common type of odontogenic tumor or hamartoma (not a true . [5] Hitchin suggested that odontomas inherited through a mutant gene or interference, possibly postnatal, with genetic control of tooth development. In humans, there is a tendency for the lamina between the tooth germs to disintegrate into clumps of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of the lamina may be an important factor in the etiology of complex or compound odontomas, and either of these may occur instead of a tooth. [5] Odontomas have been associated with trauma during primary dentition, inflammatory and infectious processes, hereditary anomalies (Gardner syndrome and Hermann syndrome), and odontoblasts hyperactivity, and alterations in the genetic components are responsible for controlling dental development. [5] According to the WHO classification (2005), two types of odontomas can be found: Complex odontomas and compound odontomas.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of odontomas is due to gene mutations or interference, or possibly postnatal genetic control of odontogenesis. Persistent dental lamina is an important factor in the aetiology of complex odontomas 10 13…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are asymptomatic and discovered during routine radiographic investigations [6, 8, 10, 12, 13, 16]. This case was found with odontoma in the wake of maxillary sinusitis symptoms such as pain and swelling.…”
Section: Discussionmentioning
confidence: 99%